2002
DOI: 10.1016/s0924-9338(02)80446-1
|View full text |Cite
|
Sign up to set email alerts
|

Duloxetine in the treatment of depression: a double-blind placebo-controlled comparison with paroxetine

Abstract: Conclusions: the achieved results point to the specific therapeutical response to different groups of antidepressive drugs in adolescence, which may be explained by psychobiological and age factors, and especially to the incomplete morphofunctional brain maturation, and with the hormone and immunological disbalance in puberty. This confirms the necessity to single out adolescent psychopharmacotherapy into a special area and to study it on different levels. Duloxetine resulted in a significant reduction in seve… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

8
139
0
3

Year Published

2006
2006
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 102 publications
(151 citation statements)
references
References 0 publications
8
139
0
3
Order By: Relevance
“…33 In the earlier study, there were no adverse events that were reported significantly more frequently in duloxetine-treated patients compared with routine care-treated patients. The study reported here provides additional evidence that duloxetine is safe for long-term therapy of patients at least 18 years old diagnosed with DPNP, and the overall safety profile reported here appears to be similar to that observed in major depressive disorder patients [22][23][24][25]38 as well as in that observed in other double-blind placebocontrolled studies of duloxetine in patients with DPNP. 27,28 …”
Section: Discussionsupporting
confidence: 83%
See 3 more Smart Citations
“…33 In the earlier study, there were no adverse events that were reported significantly more frequently in duloxetine-treated patients compared with routine care-treated patients. The study reported here provides additional evidence that duloxetine is safe for long-term therapy of patients at least 18 years old diagnosed with DPNP, and the overall safety profile reported here appears to be similar to that observed in major depressive disorder patients [22][23][24][25]38 as well as in that observed in other double-blind placebocontrolled studies of duloxetine in patients with DPNP. 27,28 …”
Section: Discussionsupporting
confidence: 83%
“…The observed increase in pulse rate for the duloxetine-treated patients could be expected due to elevations in NE tone. 37 These results are supportive of earlier clinical trials with duloxetine [22][23][24][25][27][28][29] and suggest that duloxetine has a safe cardiovascular profile. Routine care-treated patients experienced significantly higher mean changes in QT, PR, and QRS intervals compared with duloxetine-treated patients.…”
Section: Discussionsupporting
confidence: 78%
See 2 more Smart Citations
“…There are at least two reasons why a clinician thinks about using a dual action antidepressant after a SSRI failed. First, it is based on the idea that an antidepressant that has a larger spectrum of action (i.e., that simultaneously enhance both serotoninergic as well as noradrenergic systems) would be more effective than a "single" system action [9][10][11][12][13] . Second is that after a failure for an antidepressant it is generally recommended to change for a drug from another class with a different mechanism of action 14 .…”
Section: Introductionmentioning
confidence: 99%